2010
DOI: 10.1111/j.1538-7836.2009.03731.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence, risk factors and prognostic implications of venous thromboembolism in patients with gastric cancer

Abstract: Summary. Background: Data on venous thromboembolism (VTE) in gastric cancer (GC) are very scarce. Objective: To investigate the incidence, risk factors and prognostic implications of VTE in Asian GC patients. Methods: Prospective databases containing clinical information on GC patients (n = 2,085) were used. Results: The 2-year cumulative incidences of all VTE events were 0.5%, 3.5% and 24.4% in stages I, II-IV(M0) and IV(M1), respectively. Advanced stage, older age and no major surgery were independent risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(116 citation statements)
references
References 21 publications
6
106
4
Order By: Relevance
“…However, their study was not intended for operable gastric cancer. Lee et al [7] reported the incidence and risk factors of DVT in patients with both operable and inoperable gastric cancers. They reported that the 2-year cumulative incidence of VTE after diagnosis of gastric cancer was 3.8% in all patients, and 0.5%, 3.3%, 3.6%, 3.8%, and 24.4% in stages I, II, III, IV (M0), and IV (M1), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their study was not intended for operable gastric cancer. Lee et al [7] reported the incidence and risk factors of DVT in patients with both operable and inoperable gastric cancers. They reported that the 2-year cumulative incidence of VTE after diagnosis of gastric cancer was 3.8% in all patients, and 0.5%, 3.3%, 3.6%, 3.8%, and 24.4% in stages I, II, III, IV (M0), and IV (M1), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, their study was not intended for operable gastric cancer. Lee et al [7] reported the prevalence, risk factors, and prognostic implications of VTE in patients with both operable and inoperable gastric cancer. In their study, the rate of concurrent diagnosis of gastric cancer and VTE was not reported.…”
Section: Introductionmentioning
confidence: 99%
“…SNUBH is the first university hospital which has a fully digitalized system, including EMR, in Korea. The two databases contain information collected prospectively on all consecutive GC patients since the opening of SNUBH in May 2003 [22].…”
Section: Patientsmentioning
confidence: 99%
“…Incidence of VTE in our patients diagnosed with gastric cancer was found to be 14.1%. In a study performed by Lee et al that is also one of the two largest studies designed in Asian population, the frequency of VTE (symptomatic or asymptomatic) was reported to be 3.5% among a total of 2085 patients with gastric cancer 14 In the other Asian study conducted by Kang et al, VTE (symptomatic or asymptomatic) incidence was observed to be 3.3 % in 3095 patients with advanced gastric cancer. 15 Tetzlaff et al investigated the incidence of arterial and venous thrombosis during or before chemotherapy treatment in American population with advanced gastroesophageal carcinoma and reported the VTE (symptomatic or asymptomatic) incidence to be 13.6%.…”
Section: Discussionmentioning
confidence: 95%
“…13 Although the risk of thrombosis in patients with gastric cancer has been documented to be at such high rates, previous studies were limited with a small sample size and generally did not include all groups of patients with gastric cancer. 14 The initiation of extensive use of Multi-detector computed tomography in cancer patients has led to an increase in detecting of asymptomatic VTE. While anticoagulant therapy is a standard approach in the treatment of symptomatic thrombosis, it is not yet clear whether to treat asymptomatic thrombosis.…”
Section: -9mentioning
confidence: 99%